2015
DOI: 10.1111/mmi.13240
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation by Bacillus subtilis requires an endoribonuclease‐containing multisubunit complex that controls mRNA levels for the matrix gene repressor SinR

Abstract: Biofilm formation by Bacillus subtilis is largely governed by a circuit in which the response regulator Spo0A turns on the gene for the anti-repressor SinI. SinI, in turn, binds to and inactivates SinR, a dedicated repressor of genes for matrix production. Mutants of the genes ylbF, ymcA, and yaaT are blocked in biofilm formation, but the mechanism by which they act has been mysterious. A recent report attributed their role in biofilm formation to stimulating Spo0A activity. However, we detect no measurable ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(90 citation statements)
references
References 46 publications
(79 reference statements)
7
73
1
Order By: Relevance
“…; DeLoughery et al . ). Significant PyqhH and PyqhG promoter activities were observed in the lacZ analysis, compared to that of PsinI (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…; DeLoughery et al . ). Significant PyqhH and PyqhG promoter activities were observed in the lacZ analysis, compared to that of PsinI (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…It has recently been shown that the processing by RNase Y of specific mRNA targets in B. subtilis depends on the so-called Y-complex, composed of RNase Y and interacting proteins [39,40]. Overall, the exact requirements for RNase Y activity in vivo still need to be determined, and current knowledge indicates that this enzyme may exhibit various characteristics in different bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…What might be the role of the RicAFT complex in B. subtilis, beyond stimulation of the phosphorelay? DeLoughery et al (2016) have proposed that the complex modulates mRNA processing via its association with the ribonuclease Rny. Indeed they have offered persuasive evidence that in ricF and ricA null mutants, the cggR-gapA mRNA is not processed normally.…”
Section: Enhancement Of the Phosphorelay Is Not The Only Function Of mentioning
confidence: 99%